Supplementation with babassu oil reduces fatigue and inflammation in breast cancer patients: A pilot randomized clinical trial - Pereira, Paula Tâmara Vieira Teixeira; Reis, Andréa Dias [UNESP]; Silva, Surama do Carmo Sousa; Serra, Larissa de Lourdes Padilha; Leite, Richard Diego; Silva, Mayara Cristina Pinto; Lima-Aragão, Mônica Virginia Viegas; Nascimento, Flavia Raquel Fernandes; Garcia, João Batista Santos; Guerra, Rosane Nassar Meireles (Elsevier, 2020)
This study investigated the effects of babassu and coconut oil supplementation in breast cancer patients. This randomized clinical trial included 60 patients divided into three groups: untreated control group (CG), babassu oil group (BG), and coconut oil group (COG). Fatigue, quality of life, depression, tumour necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), and salivary IgA were analysed before and after 12 weeks of supplementation. Babassu supplementation decreased fatigue and improved quality of life but did not affect depression scores. Babassu also decreased TNF-α and IL-6 levels and increased IgA in saliva compared to the COG and CG. In conclusion, babassu oil supplementation reduced fatigue and improved the quality of life of breast cancer patients, and these outcomes are probably related to the immunomodulatory effects of babassu oil in reducing proinflammatory cytokines and increasing IgA antibody production. These findings indicate that babassu oil may be useful as a supplement to reduce cancer-related fatigue.
Keywords: Babassu oil; Breast cancer; Dietary supplements; Fatigue; Immunomodulation